An Objective Approach to Schizophrenia Recognition Utilizing an Adaptive Neuro-Fuzzy Inference (ANFIS) Model - Amadin, Frank; Chukwuyeni Obi, Jonathan (Transactions on Engineering and Computing Sciences, 2015)
Schizophrenia is a brain disorder that distorts the way a person thinks, acts, expresses emotions, perceives reality, and relates to others. A systematic approach and an overview perception has been carried out over the years by different researchers, but none has sufficiently introduced and Adaptive Neuro-Fuzzy Inference System (ANFIS) approach for these prediction which has served as the focal aim of this research paper using available parameters and datasets. Matric Laboratory (MATLAB) 7.0 served as the tool of implementation highlighting various views. The ANFIS training was successful completed at epoch 34, and had an error of 2.47367e-005 and the test error which was generated by the ANFIS was 0.0002511. The training was accomplished using a constant membership function type at an error tolerance at 0.05.